Understanding the life experiences of people with multiple complex needs: peer research in a health needs assessment. (26th August 2021) - Harland, Jill M; Adams, Emma A; Boobis, Sophie; Cheetham, Mandy; Wiseman, Alice; Ramsay, Sheena E
Abstract: Background: Multiple complex needs (MCN) describe a population experiencing a combination of homelessness, substance use, offending and/or mental ill-health. Using peer researchers, this study aimed to explore the perspectives of individuals with lived experience of MCN with regards to (i) issues leading to MCN and (ii) key intervention opportunities. Methods: As part of a health needs assessment in Gateshead (North East England), trained peer researchers interviewed 27 adults (aged ≥18 years) with experience of MCN, identified using purposive sampling methods. Peer researchers designed a topic guide for interviews which were audio recorded and thematically analyzed. Results: Interviewees reported adverse childhood experiences leading to MCN including abuse, bereavement, parental imprisonment, family break-up and inadequate support. Mental ill-health, substance use, poverty, early experiences of unstable housing and acute homelessness were identified as major precedents for adulthood experiences of MCN. Between 16 and 20 years, access to housing, social and mental health support was perceived as having the potential to prevent circumstances worsening. Individuals perceived removing barriers to mental health, housing and welfare and financial supports could help. Conclusions: This study highlights the perceived role austerity, adverse childhood events and current service provision have in current and future experiences of MCN. Individuals expressed a need for future interventions and support to be judgement free and provided by workers who are educated about MCN and related adversity. Involving peer researchers and individuals with experience of MCN in future research and service provision could ensure appropriate measures and supports are put in place.